(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The present study aims to identify the similarities and differences in the view of values ​​between the main social theoretical trends adopted as assets to discuss topics of interest to sociology. These trends agreed in principle to give quality of ​​objectively to the values, and differed about their interpretation, understanding and change. We resort to the comparative approach to find the disclosure of similarities and differences. This approach is the closest approaches of social research to the nature of the studied subject, mainly in the study of social phenomena. We will also turn to the analysis of the content according to the requirements of the study when determining the point of view concerning the values ​​in this direction or that as stated by the first founders of these trends, namely Emile Durkheim functional trend, and the founder of the rules of the approach in sociology, and Karl Marx, the founder of marital comprehension of history and social life, Max Weber, the founder of sociology of understanding, a pioneer of the ideal model of social analysis. The efforts made by the founders to study social problems and phenomena, which have been adopted as the basis of research in sociology, the researcher can draw from their general context their view of values ​​and reveal the underlying aspect of their studies around them, especially if we know that each of the first pioneers did not highlight directly on the values concept.